ANALYSIS OF THE EFFECT OF E-SERVICE QUALITY ON SATISFACTION CUSTOMERS OF PT BANK TABUNGAN NEGARA (PERSERO) TBK PEMATANG SIANTAR BRANCH OFFICE - Iqbal Habibie; Endang Sulistya Rini; Sugih Arto Pujangkoro (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The decrease in the number of BTN Mobile Banking users of BTN Pematang Siantar Branch Office customers needs to be analyzed, so that the cause of the decrease in BTN Mobile Banking users will be known. This study aims to test and analyze the effect of e-service quality on customer satisfaction of PT Bank Tabungan Negara (Persero) Tbk Pematang Siantar Branch Office. The population of this study was all customers of PT Bank Tabungan Negara (Persero) Tbk Pematang Siantar Branch Office, both individual customers, debtors and payroll customers who used BTN Mobile Banking in the period from January to March 2023, totaling 7,023 customers. The sample in this study was 380 people. The analysis technique used was Multiple Linear Regression Analysis. The results of statistical tests showed that efficiency, reliability, fulfillment, privacy partially influenced customer satisfaction of PT Bank Tabungan Negara (Persero) Tbk Pematang Siantar Branch Office. The results of simultaneous tests showed that efficiency, reliability, fulfillment, privacy simultaneously influenced customer satisfaction at PT Bank Tabungan Negara (Persero) Tbk Pematang Siantar Branch Office.